PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPA MELALUI MODEL PEMBELAJARAN NUMBERED HEADS TOGETHER (NHT) DI KELAS IV SD - Nanik Widyaningsih; Estuhono Estuhono (Dharmas Education Journal (DE_Journal), 2021)
This research is mainly aimed at 4th graders whose scientific level is very low at SDN 114/Bangko VII. The purpose of this study was to study how Numbered Heads Together (NHT) contributed to the improvement of students' grades. This research is one of two class action cycles. The four cycles are plan, execution, monitor, and reflect. This research was conducted by 4th grade students of SDN 114/Bangko VII. This study focuses on student learning outcomes in science class. Through tests and observations, research data were collected. This test is intended to assess the results of scientific studies conducted by students. Observation aims to capture student activities in the scientific learning process. Quantitative and qualitative analytical data were used for this study. Students in cycle 1 averaged 83, while the standard of classical value was 74%. Compared to the classical typical, 85.21 percent of students averaged in cycle two, indicating that Number Heads Together (NHT) has improved student learning in science.